'Diabetology & Metabolic Syndrome: providing an open access future for diabetes research' - Giannella-Neto, Daniel (BioMed Central, 2009)
Diabetology & Metabolic Syndrome (D&MS), the official journal of the Brazilian Diabetes Society (SBD), is a new open access, peer reviewed journal publishing research on all aspects of the pathophysiology of diabetes and metabolic syndrome. With the many ongoing and upcoming challenges for diabetes diagnosis, treatment and care, a dedicated journal providing unrestricted access for researchers and health care professionals working in the field of diabetes is needed. Diabetology & Metabolic Syndrome aims to fulfil this need.